End-stage renal disease as a risk factor for epiglottitis: a population-based cohort study in Taiwan. Issue 11 (3rd November 2020) - Tsai, Yao-Te; Tsai, Ming-Shao; Hsu, Cheng-Ming; Fang, Ku-Hao; Huang, Ethan I; Liu, Chia-Yen; Lin, Meng-Hung; Yang, Yao-Hsu; Lee, Yi-Chan; Chang, Geng-He
Abstract : Objectives: Patients with uremia are prone to infection; however, end-stage renal disease (ESRD) as a risk factor for acute epiglottitis warrants study. We investigated the risk of severe epiglottitis requiring hospitalisation in patients with ESRD. Setting: We conducted a retrospective matched cohort study by using the claims data of Taiwan's National Health Insurance Research Database. Participants: We identified an ESRD cohort with 87 908 patients newly diagnosed in 2000–2013 and underwent dialysis. The non-ESRD cohort comprised patients who had not received a diagnosis of ESRD, and they were matches to the ESRD cohort (1:1) by sex, age, residence urbanisation level, monthly income, and diabetes and hypertension status. Primary and secondary outcome measures: The cumulative incidence of epiglottitis at the end of 2013 was analysed with Kaplan-Meier methods and log-rank tests. The HR of epiglottitis was calculated using the Cox proportional hazards model after adjustment for confounding factors. Results: The overall epiglottitis incidence rate was 94% greater in the ESRD cohort than in the non-ESRD cohort (10.3 vs 5.3 cases per 100 000 person-years, p=0.002), with an adjusted HR of 1.89 (95% CI: 1.23 to 2.91, p=0.004). In the log-rank analysis, compared with the non-ESRD group, the epiglottitis cumulative incidence was significantly higher in the ESRD group (p=0.003). Epiglottitis did not exhibit an association with higher rates of airway interventions, intensive care unit admissions or longer hospitalisation in patients with ESRD than in controls. Conclusions: This nationwide matched cohort study indicated that ESRD patients should be monitored for the risk of severe epiglottitis requiring hospitalisation.